E3 Ligase Rbx1 Orchestrates Thymus Development and Fate Determination of αβ-γδ T Cells - Di Wu; Qiuxu Chen; Mingjia Tan; Yi Sun (Research)
T lymphocytes consist of αβ and γδ T cells, which mature and differentiate from the same progenitor cells in the thymus. Cullin-RING ligases (CRLs), the largest family of ubiquitin ligases, require neddylation on the scaffold protein Cullins for their ligase activity. The role of neddylation–CRL system in thymus development and fate determination of αβ/γδ T cells remains elusive. Here, we generated conditional knockout mouse models with thymus individual deletion of Ube2m or Ube2f, 2 neddylation E2-conjugating enzymes, and Rbx1 or Sag, 2 dual neddylation and ubiquitylation E3 ligases. We found that only Rbx1, but not Ube2m/Ube2f, nor Sag, plays an essential role in thymus development and fate determination of αβ/γδ T cells. Specifically, Rbx1 loss causes shrinkage of the thymus, delayed T cell development, increased γδ T cells in the thymus, increased the ratio of immature Gzma+ γδ T cells, and decreased the ratio of the proliferative subpopulation. Some of these phenotypes were moderately rescued by simultaneous Bim deletion. Mechanistically, Rbx1 loss alters the Akt, NF-κB, and metabolic pathways in progenitor γδ T cells/DN3a cells. Finally, Rbx1 loss altered the γδ T1/T17 cell population in the thymus, suggesting that Rbx1 controls the fate of γδ T cells.